Femtosecond electron and photon pulses facility in Thailand - S. Rimjaem (2018)
Femtosecond electron and photon pulses facility has been established as SURIYA project at the Fast Neutron Research Facility (FNRF). Femtosecond electron bunches can be generated from a system consisting of an RF gun with a thermionic cathode, an alpha magnet as an magnetic bunch compressor, and a linear accelerator as a post acceleration section. Femtosecond electron pulses can be used directly or used as a source to produce equally short electromagnetic (EM) radiation pulses via certain kind of radiation production processes. At SURIYA project, we are interested especially in production of radiation in Far-infrared (FIR) regime. At these wavelengths, the radiation from femtosecond electron pulses is emitted coherently resulting in high intensity radiation. Overview of the facility, the generation of femtosecond electron bunches, the theoretical background of coherent transition radiation and the recent experimental results will be presented and discussed in this paper. © 2007 American Institute of Physics.